THE CURRENT STATE OF TEACHING FOLKLORIC WORKS IN HIGHER EDUCATION INSTITUTIONS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article analyzes the current state of teaching folkloric works in higher education institutions, with a focus on existing pedagogical approaches and the challenges encountered in practice. In particular, it examines the role of oral folk literature in academic curricula, the application of innovative teaching methods in conveying such materials to students, and the means of enhancing educational effectiveness. Additionally, the article highlights the educational significance of folklore materials in shaping national identity and spiritual values. Based on the analysis, recommendations and proposals are offered to improve the quality of folklore instruction in the higher education system.